Validation study of human figure drawing test in a Colombian school children population (2011)
The aim of this article was to assess the validity of the emotional and developmental components of the Koppitz human figure drawing test. 2420 children's drawings available in a database resulting from a previous cross sectional study designed to determine the prevalence of neurological diseases in children between 0 and 12 years old in Bogota schools were evaluated. They were scored using the criteria proposed by Koppitz, and classified into 16 groups according to age, gender, and presence/absence of learning or attention problems. The overall results were then compared with the normative study to assess whether descriptive parameters of the two populations were significantly different. There were no significant differences associated with presence/absence of learning and attention disorders or school attended within the overall sample. An Interrater reliability test has been made to assure the homogeneity of scoring by the evaluator team. There were significant differences between this population and that of the original study. New scoring tables contextualized for our population based on the frequency of appearance in this sample are presented. We can conclude that various ethnic, social, and cultural factors can influence the way children draw the human figure. It is thus important to establish local reference values to adequately distinguish between normality and abnormality. The new scoring tables proposed here should be followed up with a clinical study to corroborate their validity. © 2011 by The Spanish Journal of Psychology.